The Effect Of Profitability And Profit Volatility On Capital Structure In Cyclical And Non-Cyclical Consumer Companies Listed On The Indonesia Stock Exchange - Fitriani fitriani; Ramel Yanuarta RE (Financial Management Studies, 2022)
The purpose of this study is to analyze the effect of profitability and earnings volatility on the capital structure of cyclical and non-cyclical consumer companies listed on the Indonesia Stock Exchange. The population in this study are all cyclical and non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2016-2021. In this study, the sample selection method used purposive sampling method. The sample in this study were 125 companies where 68 consumer cyclical companies and 57 non-cyclical companies with 750 observations for each variable. The analytical method used is panel data regression analysis. This study uses the Stata program as a tool in analyzing the data. The results of this study indicate that there is a significant difference between the capital structure of cyclical and non-cyclical consumer companies, profitability has a positive and significant effect on the capital structure of cyclical and non-cyclical consumer companies, earnings volatility has a positive and significant effect on the capital structure of cyclical consumer companies. and non-cyclical.